Analisis Pemutusan Hubungan Kerja Secara Sepihak dengan Perjanjian Kerja Kemitraan Menurut Hukum Ketenagakerjaan - Michael Kalep Simarmata; Rasji (Jurnal Hukum Lex Generalis, 2024)
Arbitration is increasingly recognized as an effective forum for dispute resolution. One of the key advantages of arbitration is its principle of finality and binding nature, which limits the availability of legal remedies. However, Article 70 of the Indonesian Arbitration Act paves the way for parties to submit an application for annulment of arbitral awards to the District Court, but only on specific, limited grounds. Furthermore, a party may appeal to the Supreme Court regarding the annulment of arbitration awards issued by the District Court, positioning the Supreme Court as the final arbiter in such cases. In practice, there have been instances where the Supreme Court has misapplied the law, seemingly disregarding evidence acknowledged by the District Court. This has led to significant legal uncertainty. This study aims to identify the legal misapplications made by the Supreme Court during the appeal process for annulment of arbitral awards. Utilizing a normative research methodology, this research analyzes existing laws and regulations to address these issues. The findings conclude that one of the legal standards applied by the Supreme Court during the appeal stage contradict Indonesia's arbitration law, undermining the integrity of the arbitration process.